2023
DOI: 10.3390/buildings13112730
|View full text |Cite
|
Sign up to set email alerts
|

Bridge Condition Deterioration Prediction Using the Whale Optimization Algorithm and Extreme Learning Machine

Liming Jiang,
Qizhi Tang,
Yan Jiang
et al.

Abstract: To address the problem in model computations and the limited accuracy of current bridge deterioration prediction methods, this paper proposes a novel bridge deterioration prediction meth-od using the whale optimization algorithm and extreme learning machine (WOA-ELM). First, we collected a dataset consisting of 539 sets of bridge inspection data and determined the necessary influencing factors through correlation analysis. Subsequently, the WOA-ELM algorithm was applied to establish a nonlinear mapping relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…Jiang et al [27] obtained the deterioration of a bridge through the hybrid method of whale algorithm with other machine learning. The results demonstrated that the com-bined model performed better than the simple model.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al [27] obtained the deterioration of a bridge through the hybrid method of whale algorithm with other machine learning. The results demonstrated that the com-bined model performed better than the simple model.…”
Section: Introductionmentioning
confidence: 99%